High-thermal-conductivity ceramic-based composite material and preparation method thereof
By introducing BN in ceramic matrix composite materials using carbon nanotube fiber braiding and specific sanding and high-pressure homogeneous dispersion technology, the problems of low thermal conductivity and waste of process after forming are solved, and efficient heat transfer and high thermal conductivity of the material are achieved.
Patent Information
- Application Number
- CN202411754259.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The thermal conductivity of existing ceramic matrix composite materials is low, resulting in the inability to effectively and quickly disperse heat in extreme environments. Traditional preparation techniques lead to waste and fiber breakage problems when the materials are processed after forming.
Carbon nanotube fibers are used to obtain a preform, and uniformly dispersed BN is introduced into the SiBCN ceramic matrix as a high thermal conductivity phase through specific sand milling and high-pressure homogeneous dispersion technology to form a π-π stacking force to avoid agglomeration of BN powders, thereby improving the thermal conductivity of the ceramic matrix composite material.
It realizes high thermal conductivity of ceramic matrix composite materials, can transmit heat in a directional and rapid directional and internal heat, solves the problem of insufficient thermal conductivity in traditional technology, and reduces waste of reprocessing after forming and fiber breakage.
Smart Images

Figure CN119569472A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a high thermal conductivity ceramic-based composite material and a preparation method thereof. Background Art
[0002] As a new type of material, ceramic matrix composites mainly include fibers, interface layers, and ceramic matrices, and have many advantages such as high temperature resistance, light weight, and high toughness. Inside ceramic matrix composites, the thermal conductivity of ceramic matrix and carbon fiber is generally low, which makes the heat too concentrated in the local part of the material, and cannot be effectively and quickly conducted, resulting in excessive temperature and exceeding its temperature resistance limit. In view of the problem of low thermal conductivity of the ceramic matrix, a high thermal conductivity phase can be added inside it to improve its thermal conduction efficiency. For example, high thermal conductivity components such as graphene, carbon nanotubes, and boron nitride (BN) can be added to the existing ceramic precursor. However, there is also the problem of uneven distribution of high thermal conductivity components in the precursor, mainly because their surface tension is large and they are easy to agglomerate and cannot be evenly dispersed. Therefore, how to further improve the thermal conductivity of ceramic matrix composites and ensure their thermal properties under extreme environments has become a key research issue in this technical field.
[0003] In addition, the thermal conductivity of mesophase asphalt-based carbon fiber can reach 800W / m·K, while the thermal conductivity of conventional PAN-based carbon fiber is only 20-60W / m·K. The ultra-high thermal conductivity makes the mesophase asphalt-based carbon fiber and the ceramic matrix composite material have significant advantages in thermal conduction. However, due to the large modulus of the general mesophase asphalt-based fiber, the fiber diameter of the general mesophase asphalt-based carbon fiber can generally reach 14μm, and the flexibility is relatively poor, which is difficult to meet the large bending, resulting in the existing preforms woven with mesophase asphalt-based carbon fiber and / or PAN-based carbon fiber are usually flat preforms. However, the ceramic-based composite material currently made of this conventional structural preform is in the shape of a flat plate, and this conventional shape cannot meet the application requirements in certain specific scenarios. In order to obtain a ceramic-based composite material of a specific shape, the traditional preparation technology is usually to prepare a flat ceramic-based composite material first, and then process it into a specific shape. This method that requires reprocessing leads to a large waste of ceramic-based composite materials and fiber breakage, and the problem of fiber discontinuity, which ultimately leads to the ceramic-based composite material of a specific shape prepared by traditional technology. There are deficiencies in thermal conduction and / or mechanical properties.
[0004] In summary, it is very necessary to provide a high thermal conductivity ceramic-based composite material and a preparation method thereof. Summary of the invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a high thermal conductivity ceramic-based composite material and a preparation method thereof. The method of the present invention uses carbon nanotube fibers to weave a preform, gives full play to the high flexibility and high thermal conductivity of carbon nanotube fibers, and introduces uniformly dispersed BN as a high thermal conductivity phase in the SiBCN ceramic matrix through specific sand grinding and high-pressure homogenization dispersion technology, realizes the formation of π-π stacking force between the boron nitrogen ring and the few-layer BN in the SiBCN precursor, effectively avoids the agglomeration of BN powder, so that the few-layer BN can be evenly dispersed in the SiBCN precursor, thereby further improving the thermal conductivity of the ceramic-based composite material, and can realize the directional and rapid transmission of heat inside the ceramic-based composite material, solving the problem of poor thermal conductivity of the ceramic-based composite material prepared by traditional technology.
[0006] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material with high thermal conductivity, the method comprising the following steps:
[0007] (1) preparing a carbon nanotube fiber preform;
[0008] (2) preparing a pyrolytic carbon interface layer on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition to obtain a carbon nanotube fiber preform having a pyrolytic carbon interface layer;
[0009] (3) uniformly dispersing boron nitride in a SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor solution;
[0010] (4) reacting the BN / SiBCN precursor solution with the carbon nanotube fiber preform having a pyrolytic carbon interface layer obtained in step (3) through a precursor impregnation and cracking process to obtain a ceramic-based composite material with high thermal conductivity.
[0011] Preferably, in step (1), the carbon nanotube fiber preform used has a thermal conductivity of 400 to 1000 W / (m·K), a tensile strength of 3 to 5 GPa, and an elongation at break of 2.5 to 4%; and / or the carbon nanotube fiber preform has a density of 0.5 to 0.9 g / cm 3 .
[0012] Preferably, in step (2): the thickness of the pyrolytic carbon interface layer is 0.1-2 μm.
[0013] Preferably, step (3) is: adding boron nitride to the SiBCN precursor solution and sand milling to obtain a coarse dispersion, and then high-pressure homogenizing and dispersing the coarse dispersion to obtain a fine dispersion, namely the BN / SiBCN precursor solution; the sand milling time is 30 to 60 minutes, the sand milling speed is 1000-3000r / min, the particle size of the zirconium beads used in the sand milling is 1 to 3mm, and the zirconium bead filling rate is 50-70%; the pressure of the high-pressure homogenizing dispersion is 35 to 100MPa, the high-pressure homogenizing dispersion time is 15 to 60 minutes, and the temperature is 25 to 60°C.
[0014] Preferably, in step (3): the boron nitride is a few-layer boron nitride, the particle size of the few-layer boron nitride is 0.1-1 μm, and the number of layers is 1 to 10 layers; the solid content of the SiBCN precursor solution is 45%, and the viscosity is 10 mPa·s; and / or the solid content of the BN / SiBCN precursor solution is 50-65%, and the viscosity is 50-100 mPa·s.
[0015] Preferably, step (4) includes the following sub-steps: (a) placing the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step (3) in a BN / SiBCN precursor solution and immersing it for 30 to 360 minutes to obtain a material impregnated with the BN / SiBCN precursor; preferably, the impregnation is vacuum impregnation and pressure impregnation; (b) curing the material impregnated with the BN / SiBCN precursor solution, and then placing it in a reaction device, sealing, evacuating, introducing inert gas, and cracking it at 1000 to 1500°C for 20 to 200 minutes; preferably, the curing is curing at 150 to 350°C for 30 to 360 minutes; (c) after the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped and the pressure is restored to atmospheric pressure; (d) repeating steps (a) to (c) at least once, preferably 1 to 10 times.
[0016] Preferably, in step (1): the carbon nanotube fiber preform is a pointed wedge-shaped carbon nanotube fiber preform, and the pointed wedge-shaped carbon nanotube fiber preform is prepared by: mixing carbon nanotube fibers with PAN-based carbon fibers to obtain a carbon nanotube fiber / carbon fiber bidirectional cloth, and then using a lamination and stitching process to make the carbon nanotube fiber / carbon fiber bidirectional cloth into a pointed wedge-shaped carbon nanotube fiber preform.
[0017] Preferably, in the carbon nanotube fiber / carbon fiber bidirectional fabric, the carbon nanotube fibers and the PAN-based carbon fibers are vertically distributed; and / or the surface density of the carbon nanotube fiber / carbon fiber bidirectional fabric is 300-400 g / m 2 .
[0018] Preferably, the lamination and stitching process is: first folding the carbon nanotube fiber / carbon fiber bidirectional cloth in a direction perpendicular to the carbon nanotube fiber, and then stacking and stitching a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths to obtain a pointed wedge-shaped carbon nanotube fiber preform; and / or the volume ratio of carbon nanotube fibers to PAN-based carbon fibers in the pointed wedge-shaped carbon nanotube fiber preform is (1-3): (1-3); and / or the density of the pointed wedge-shaped carbon nanotube fiber preform is 0.6-0.9 g / cm 3 .
[0019] In a second aspect, the present invention provides a ceramic-based composite material with high thermal conductivity prepared by the preparation method described in the first aspect of the present invention.
[0020] Preferably, the density of the high thermal conductivity ceramic-based composite material is 2.2-2.8 g / cm 3 ; and / or the high thermal conductivity ceramic-based composite material has a thermal conductivity of 300 to 500 W / (m·K) and a tensile strength of 160 to 220 MPa in an inert atmosphere at room temperature.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects:
[0022] (1) The present invention realizes the weaving of carbon nanotube fiber preforms by giving full play to the high flexibility and high thermal conductivity of carbon nanotube fibers; compared with PAN-based carbon fibers and mesophase asphalt-based carbon fibers, carbon nanotube fibers have significant advantages in thermal conductivity and flexibility, and construct a network structure that quickly transmits heat; the present invention can achieve controllable regulation of the thermal conductivity of the finally prepared ceramic-based composite material by regulating the volume ratio of carbon nanotube fibers.
[0023] (2) The present invention can evenly disperse BN in a SiBCN precursor to form a BN / SiBCN precursor solution by adopting specific sand milling and high-pressure homogenization dispersion technology; the present invention finds that the thermal conductivity of BN is extremely high, up to 1000W / (m·K), and its uniform distribution in ceramics can significantly improve the thermal conductivity of ceramic-based composite materials; the present invention finds that the boron nitrogen ring in the SiBCN precursor molecule has a conjugated π bond, and the few-layer BN also has a conjugated π bond. Through specific sand milling and high-pressure homogenization dispersion technology, the boron nitrogen ring and the few-layer BN can form a π-π stacking force, which can effectively avoid the agglomeration of BN powder, thereby evenly dispersing the few-layer BN in the SiBCN precursor.
[0024] (3) In some preferred embodiments of the present invention, a fiber preform of a novel structure is designed, that is, a pointed wedge-shaped carbon nanotube fiber preform is used as a preform for a ceramic-based composite material. The main structural feature of the pointed wedge-shaped carbon nanotube fiber preform in the present invention is that along a certain fiber direction, the surface of the preform gradually becomes pointed, and the geometric shape is a pointed wedge (a shape in which one end of the preform is pointed and the other end is thick). The present invention finds that the use of such a pointed wedge-shaped preform can obtain a directly integrated pointed wedge-shaped ceramic-based composite material. The pointed wedge-shaped ceramic-based composite material has better structural adaptability and functionality in specific application scenarios, and the pointed wedge-shaped structure can improve the stress distribution and local strengthening effect of the material. In some applications, the pointed wedge shape is helpful for optimizing fluid flow. Reduce friction resistance, especially in the fields of aerospace, power machinery, etc. The pointed wedge-shaped structure can effectively improve the flow state of air and liquid flow, improve energy efficiency, and can better disperse the concentrated area of external force, reduce crack propagation, and improve fatigue resistance under high temperature and high pressure environment; in addition, the present invention can realize the weaving of the pointed wedge-shaped carbon nanotube fiber preform through the mixed weaving of carbon nanotube fibers and carbon fibers, which gives full play to the high flexibility and high thermal conductivity of carbon nanotube fibers, while pure PAN-based and general asphalt-based carbon fibers cannot meet the design requirements due to their poor flexibility; and the present invention can realize the controllable adjustment of the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material by regulating the volume ratio of carbon nanotube fibers to carbon fibers in the pointed wedge-shaped carbon nanotube fiber preform.
[0025] (4) The present invention preferably uses a pointed wedge-shaped carbon nanotube fiber preform to directly integrate and form a pointed wedge-shaped ceramic-based composite material, which can take into account both fiber continuity and cost economy, and better ensure the thermal conductivity and mechanical properties of the ceramic-based composite material. This is also something that cannot be achieved by using a ceramic-based composite material made of a conventional structural preform and then processing it into a pointed wedge-shaped product after molding. This is because the method of first molding the ceramic-based composite material and then processing it into a product of a specific shape will cause the fibers in the tip area of the product to no longer be continuous. At the same time, there is a large waste in the preparation process, which leads to higher costs, and there are problems with the thermal conductivity, ablation resistance and mechanical properties of the prepared ceramic-based composite material being insufficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of a pointed wedge-shaped carbon nanotube fiber preform obtained in some specific embodiments of the present invention;
[0027] Figure 2 It is a schematic diagram of the pointed wedge-shaped carbon nanotube fiber preform obtained in some specific embodiments of the present invention at another angle. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. In a first aspect, the present invention provides a method for preparing a ceramic-based composite material with high thermal conductivity, the method comprising the following steps:
[0029] (1) preparing a carbon nanotube fiber preform; in some specific embodiments, for example, continuous carbon nanotube fibers are provided, and then conventional weaving processes such as stitching and puncturing are used to weave the carbon nanotube fibers to obtain a carbon nanotube fiber preform; in the present invention, by adjusting the volume ratio of the carbon nanotube fibers, the thermal conductivity of the ceramic matrix composite material finally prepared can be controlled and adjusted;
[0030] (2) preparing a pyrolytic carbon interface layer on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition to obtain a carbon nanotube fiber preform having a pyrolytic carbon interface layer (also referred to as a porous carbon / carbon matrix); the present invention does not specifically limit the process conditions of the chemical vapor deposition method, and those skilled in the art can routinely select;
[0031] (3) Boron nitride is uniformly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor solution; the present invention is to use specific sand milling and high-pressure homogenization dispersion technology to more uniformly disperse boron nitride (BN) in the SiBCN precursor solution, which is not achievable by existing stirring and / or ultrasonic dispersion technology; the present invention finds that the reason why boron nitride (BN) can be more uniformly dispersed in the SiBCN precursor solution by the sand milling and high-pressure homogenization dispersion technology described in the present invention is that there is a boron nitrogen ring in the SiBCN precursor molecule, and its molecular structure is as follows: As shown in the figure, there are conjugated π bonds in the boron nitrogen ring in the SiBCN precursor molecule, and there are also conjugated π bonds in the few-layer BN. Through sand grinding and high-pressure homogenization dispersion technology, the boron nitrogen ring and the few-layer BN can form a π-π stacking force. Through high-pressure homogenization dispersion technology, extremely high pressure can promote the boron nitrogen ring in the SiBCN molecular structure to form a π-π stacking force with the few-layer BN, effectively avoiding the agglomeration of BN powder, so that the few-layer BN can be more evenly dispersed in the SiBCN precursor solution. However, by conventional stirring and ultrasonic treatment, the force between the BN powder flakes cannot be effectively overcome, and large agglomerates still exist.
[0032]
[0033] (4) reacting the BN / SiBCN precursor solution with the carbon nanotube fiber preform having a pyrolytic carbon interface layer obtained in step (3) through a precursor impregnation and pyrolysis process to obtain a ceramic-based composite material with high thermal conductivity; that is, in step (4), the BN / SiBCN precursor solution is used as a reactant to compound the carbon nanotube fiber preform having a pyrolytic carbon interface layer obtained in step (3), and the ceramic-based composite material with high thermal conductivity is prepared by a precursor impregnation and pyrolysis method; in the present invention, the high thermal conductivity of the ceramic-based composite material obtained, for example, refers to a thermal conductivity of 300 to 500 W / (m·K) at room temperature.
[0034] The present invention realizes the weaving of carbon nanotube fiber preforms by giving full play to the high flexibility and high thermal conductivity of carbon nanotube fibers; compared with PAN-based carbon fibers and mesophase asphalt-based carbon fibers, carbon nanotube fibers have significant advantages in thermal conductivity and flexibility, and construct a network structure that quickly transmits heat; the present invention can achieve controllable adjustment of the thermal conductivity of the finally prepared ceramic-based composite material by regulating the volume ratio of carbon nanotube fibers. The present invention can evenly disperse BN in a SiBCN precursor to form a BN / SiBCN precursor solution by adopting specific sand milling and high-pressure homogenization dispersion technology; the present invention finds that the thermal conductivity of BN is extremely high, which can reach 1000W / (m·K), and BN is evenly distributed in ceramics, which can significantly improve the thermal conductivity of ceramic-based composite materials; the present invention finds that the boron nitrogen ring in the SiBCN precursor molecule has a conjugated π bond, and the few-layer BN also has a conjugated π bond. Through the specific sand milling and high-pressure homogenization dispersion technology, the boron nitrogen ring and the few-layer BN can form a π-π stacking force, which can effectively avoid the agglomeration of BN powder, so that the few-layer BN can be evenly dispersed in the SiBCN precursor.
[0035] According to some preferred embodiments, in step (1): the carbon nanotube fiber preform used in the carbon nanotube fiber (continuous carbon nanotube fiber) has a thermal conductivity of 400 to 1000 W / (m·K), a tensile strength of 3 to 5 GPa, an elongation at break of 2.5 to 4%, and a density of 1.4 to 1.5 g / cm 3 ; In the present invention, it is preferred to use carbon nanotube fibers with a breaking elongation of 2.5-4% and a thermal conductivity of 400-1000 W / (m·K), indicating that they have excellent high flexibility and high thermal conductivity; The present invention does not specifically limit the source of the carbon nanotube fibers, and directly purchased products or products synthesized by existing methods can be used; In the present invention, for example, products purchased from the Suzhou Institute of Nano-Tech and Nano-Bionics, Chinese Academy of Sciences can be used.
[0036] According to some preferred embodiments, the density of the carbon nanotube fiber preform is 0.5 to 0.9 g / cm 3 .
[0037] According to some preferred embodiments, in step (2): the thickness of the pyrolytic carbon interface layer is 0.1 to 2 μm; in the present invention, it is preferred to control the thickness of the pyrolytic carbon interface layer to be 0.1 to 2 μm, so that the pore size of the preform can be regulated. When the thickness of the pyrolytic carbon interface layer is lower than 0.1 μm, the internal pore size is larger, but it is easy to cause the buffer layer between the carbon nanotube fiber and the ceramic matrix to be weak, resulting in poor mechanical properties of the composite material; when the thickness of the pyrolytic carbon interface layer is higher than 2 μm, the internal pore size is smaller, and it is difficult to satisfy the smooth impregnation of a few layers of BN, resulting in poor filling effect of the few layers of BN, and the thermal conductivity of the composite material cannot be effectively improved.
[0038] According to some preferred embodiments, step (3) is: adding boron nitride to the SiBCN precursor solution and sand-milling to obtain a coarse dispersion, and then high-pressure homogenizing and dispersing the coarse dispersion to obtain a fine dispersion, namely the BN / SiBCN precursor solution; the sand-milling time is 30 to 60 minutes, the sand-milling speed is 1000-3000r / min, the sand-milling is carried out in a sand mill, the filling medium is zirconium beads (zirconia beads), the particle size of the zirconium beads used in the sand-milling is 1 to 3 mm, and the zirconium bead filling rate is 50-70%; the pressure of the high-pressure homogenizing dispersion is 35 to 100 MPa, the time of the high-pressure homogenizing dispersion is 15 to 60 minutes, and the temperature is 25 to 60°C; in the present invention, the high-pressure homogenizing dispersion is carried out, for example, in a high-pressure homogenizer.
[0039] In the present invention, the BN and SiBCN precursor solutions are first coarsely dispersed by sand milling technology under the above-mentioned appropriate specific sand milling conditions, and then the coarse dispersion obtained is finely dispersed by high-pressure homogenous dispersion technology under appropriate specific high-pressure homogenous dispersion conditions. This is beneficial to ensure that the boron nitrogen ring and the few-layer BN form a π-π stacking force, which can effectively avoid the agglomeration of BN powder, thereby uniformly dispersing the few-layer BN in the SiBCN precursor.
[0040] According to some preferred embodiments, in step (3): the boron nitride (boron nitride powder) is a few-layer boron nitride, the particle size of the few-layer boron nitride is 0.1-1 μm, and the number of layers is 1 to 10 layers; in the present invention, the boron nitride can be purchased commercially; the solid content of the SiBCN precursor solution is 45%, and the viscosity is 10 mPa·s; in the present invention, the SiBCN precursor solution is prepared using an organic solvent and a SiBCN precursor, and the organic solvent can be, for example, xylene and / or toluene, and the SiBCN precursor is polyborosilazane. Preferably, the present invention uses an organic solvent to prepare polyborosilazane. The SiBCN precursor solution is prepared with polyborosilazane to have a solid content of 45% and a viscosity of 10 mPa·s; the present invention does not specifically limit the source of polyborosilazane, and can use products that can be directly purchased or products synthesized by existing methods; and / or the solid content of the BN / SiBCN precursor solution is 50-65%, and the viscosity is 50-100 mPa·s; in the present invention, the amount of the boron nitride powder is such that the solid content of the SiBCN precursor solution after adding the boron nitride powder reaches 50-65%, and the viscosity is 50-100 mPa·s; the present invention can adjust BN by adding different contents of BN The solid content of the N / SiBCN precursor solution can effectively regulate the viscosity of the solution, thereby also affecting the content of BN in the composite material, and realizing the regulation of the thermal conductivity of the composite material; the present invention preferably has a solid content of 50-65% and a viscosity of 50-100 mPa·s for the BN / SiBCN precursor solution. The present invention finds that when the solid content of the BN / SiBCN precursor solution is lower than 50%, its viscosity is lower, and the BN content is lower, and the thermal conductivity of the ceramic-based composite material cannot be significantly improved. When the solid content of the BN / SiBCN precursor solution is higher than 65%, the proportion of BN in the solution is higher, which increases the viscosity of the solution. , unable to effectively fill the internal pores, resulting in poor impregnation effect, resulting in low density of the ceramic-based composite material, and ultimately affecting the thermal conductivity and mechanical properties of the ceramic-based composite material; the present invention adopts the BN / SiBCN precursor solution with a solid content of 50-65% and a viscosity of 50-100mPa·s for subsequent precursor impregnation and cracking technology, so as to achieve the adjustment of the BN content in the ceramic-based composite material. Since the thermal conductivity of BN can reach 1000W / (m·K), and in the present invention, a more uniform distribution of BN in the SiBCN precursor solution can be achieved, the thermal conductivity of the ceramic-based composite material can be significantly improved.
[0041] The present invention does not specifically limit the impregnation, curing and cracking conditions used in the precursor impregnation, curing and cracking process, and those skilled in the art can make routine selections.
[0042] According to some preferred embodiments, in step (4):
[0043] (a) placing the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step (3) in a BN / SiBCN precursor solution and immersing it for 30 to 360 minutes, and filling the BN / SiBCN precursor solution into the pores inside the carbon nanotube fiber preform with a pyrolytic carbon interface layer to obtain a material impregnated with a BN / SiBCN precursor; preferably, the impregnation is vacuum impregnation and pressure impregnation; the present invention does not specifically limit the process parameters of vacuum impregnation and pressure impregnation, which are well known to those skilled in the art and can be carried out using conventional parameters;
[0044] (b) curing the material impregnated with the BN / SiBCN precursor solution, specifically, for example, curing can be carried out under an inert atmosphere such as argon and a heating condition of 150-350° C., so that the BN / SiBCN precursor solution inside the pores can be cross-linked and cured, and then the cured material is placed in a reaction device, sealed, evacuated, and an inert gas such as argon is introduced, the flow rate can be, for example, 100-5000 sccm, and the temperature is controlled by program control, and the cracking is carried out at 1000-1500° C. for 20-200 min; preferably, the curing is cured at 150-350° C. for 30-360 min; in the present invention, the heating rate to 150-350° C. and / or 1000-1500° C. can be, for example, 0.1-10° C. / min;
[0045] (c) After the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped, and the temperature is restored to atmospheric pressure; in the present invention, the rate of the temperature reduction can be, for example, 1 to 10° C. / minute;
[0046] (d) Repeating steps (a) to (c) at least once, preferably 1 to 10 times.
[0047] According to some preferred embodiments, in step (1): the carbon nanotube fiber preform is a pointed wedge-shaped carbon nanotube fiber preform. In the present invention, the structure of the pointed wedge-shaped carbon nanotube fiber preform can be, for example, Figure 1 and Figure 2 As shown; the preparation of the pointed wedge-shaped carbon nanotube fiber preform is: mixing carbon nanotube fibers with PAN-based carbon fibers to obtain carbon nanotube fiber / carbon fiber bidirectional cloth, and then using a lamination and stitching process to make the carbon nanotube fiber / carbon fiber bidirectional cloth into a pointed wedge-shaped carbon nanotube fiber preform; in the present invention, when a pointed wedge-shaped carbon nanotube fiber preform is used, the obtained high thermal conductivity ceramic-based composite material is in a pointed wedge shape; in the present invention, the carbon nanotube fibers are continuous carbon nanotube fibers, and the PAN-based carbon fibers are PAN-based continuous carbon fibers.
[0048] The present invention preferably designs a fiber preform of a novel structure, that is, a pointed wedge-shaped carbon nanotube fiber preform is used as a preform for a ceramic-based composite material. The main structural feature of the pointed wedge-shaped carbon nanotube fiber preform in the present invention is that along a certain fiber direction, the surface of the preform gradually becomes pointed, and the geometric shape is a pointed wedge (a shape in which one end of the preform is pointed and the other end is thick). One end of the pointed wedge-shaped carbon nanotube fiber preform of the present invention is a pointed end region, and the other end is a thick end region. The present invention finds that the use of such a pointed wedge-shaped preform can obtain a directly integrated pointed wedge-shaped ceramic-based composite material. The pointed wedge-shaped ceramic-based composite material has better structural adaptability and functionality in specific application scenarios, and the pointed wedge-shaped structure can improve the stress distribution and local strengthening effect of the material. In certain applications, the pointed wedge shape The shape helps to optimize fluid flow and reduce friction resistance, especially in the fields of aerospace, power machinery, etc. The pointed wedge-shaped structure can effectively improve the flow state of airflow and liquid flow, improve energy efficiency, and can better disperse the concentrated area of external force, reduce crack propagation, and improve fatigue resistance under high temperature and high pressure environment; in addition, the present invention can realize the weaving of the pointed wedge-shaped carbon nanotube fiber preform through the mixed weaving of carbon nanotube fibers and carbon fibers, which gives full play to the high flexibility and high thermal conductivity of carbon nanotube fibers, while pure PAN-based and general asphalt-based carbon fibers cannot meet the design requirements due to their poor flexibility; and the present invention can realize the controllable adjustment of the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material by regulating the volume ratio of carbon nanotube fibers to carbon fibers in the pointed wedge-shaped carbon nanotube fiber preform. The present invention preferably uses a pointed wedge-shaped carbon nanotube fiber preform to directly integrate and form a pointed wedge-shaped ceramic-based composite material, which can take into account both fiber continuity and cost economy, and better ensure the thermal conductivity and mechanical properties of the ceramic-based composite material. This is also something that cannot be achieved by using a ceramic-based composite material made of a conventional structural preform and then processing it into a pointed wedge-shaped product after molding. This is because this method of first molding the ceramic-based composite material and then processing it into a product of a specific shape will cause the fibers in the tip area of the product to no longer be continuous. At the same time, there is a large waste in the preparation process, and there are problems with the thermal conductivity, ablation resistance and mechanical properties of the prepared ceramic-based composite material being insufficient.
[0049] According to some preferred embodiments, the thermal conductivity of the carbon nanotube fiber used in the pointed wedge-shaped carbon nanotube fiber preform is 400-1000 W / (m·K), the tensile strength is 3-5 GPa, the elongation at break is 2.5-4%, and the density is 1.4-1.5 g / cm 3; In the present invention, it is preferred to use carbon nanotube fibers with a breaking elongation of 2.5-4% and a thermal conductivity of 400-1000 W / (m·K), indicating that they have excellent flexibility and can meet the requirements of nearly 180° bending in the tip area of the pointed wedge-shaped carbon nanotube fiber preform without breaking, thereby realizing the weaving of the pointed wedge-shaped carbon nanotube fiber preform, which is impossible for PAN-based carbon fibers and general intermediate phase asphalt-based carbon fibers.
[0050] According to some preferred embodiments, in the carbon nanotube fiber / carbon fiber bidirectional cloth, the carbon nanotube fibers and the PAN-based carbon fibers are vertically distributed, that is, when the carbon nanotube fiber / carbon fiber bidirectional cloth is mixed, the carbon nanotube fibers and the PAN-based carbon fibers are perpendicular to each other; and / or the surface density of the carbon nanotube fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 When the carbon nanotube fiber / carbon fiber bidirectional cloth is mixed in the present invention, the ratio of carbon nanotube fiber to PAN-based carbon fiber can be adjusted to meet the subsequent weaving of a pointed wedge-shaped carbon nanotube fiber preform having a specific volume ratio of carbon nanotube fiber to PAN-based carbon fiber.
[0051] According to some preferred embodiments, the lamination and stitching process is: first fold the carbon nanotube fiber / carbon fiber bidirectional cloth in a direction perpendicular to the carbon nanotube fiber, and then stack and stitch multiple (two or more) folded carbon nanotube fiber / carbon fiber bidirectional cloths to obtain a pointed wedge-shaped carbon nanotube fiber preform; in the present invention, when laminating, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloth correspond to the tips, and the thick ends correspond to the thick ends, and then PAN-based carbon fibers are used to stitch the multiple folded carbon nanotube fiber / carbon fiber bidirectional cloths into one; the present invention does not make specific limitations on the stitching method used, and technicians in this field can make conventional choices, for example, an orthogonal stitching method can be used; the present invention does not make specific limitations on the number of carbon nanotube fiber / carbon fiber bidirectional cloths used for lamination, and technicians in this field can make conventional choices based on the thickness requirements of the pointed wedge-shaped carbon nanotube fiber preform.
[0052] According to some preferred embodiments, the volume ratio of carbon nanotube fibers to PAN-based carbon fibers in the pointed wedge-shaped carbon nanotube fiber preform is (1-3): (1-3); and / or the density of the pointed wedge-shaped carbon nanotube fiber preform is 0.6-0.9 g / cm 3; In the present invention, by controlling the volume ratio of the carbon nanotube fibers in the pointed wedge-shaped carbon nanotube fiber preform, the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material can be effectively regulated. In the present invention, preferably, the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers in the pointed wedge-shaped carbon nanotube fiber preform is (1-3): (1-3), which is conducive to ensuring that the high thermal conductivity ceramic-based composite material with both high thermal conductivity and excellent mechanical properties is obtained; The present invention finds that if the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers is lower than 1:3, the mechanical properties and thermal conductivity of the finally prepared ceramic-based composite material in the direction of the carbon nanotube fibers will be lower. If the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers is higher than 3:1, the mechanical strength of the finally prepared ceramic-based composite material in the direction of the carbon fibers will be lower.
[0053] In the second aspect, the present invention provides a high thermal conductivity ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention; the high thermal conductivity ceramic-based composite material prepared by the present invention has the characteristics of high thermal conductivity, which is manifested in the high thermal conductivity and high tensile strength of the composite material.
[0054] According to some preferred embodiments, the density of the high thermal conductivity ceramic-based composite material is 2.2 to 2.8 g / cm 3 ; and / or the high thermal conductivity ceramic-based composite material has a thermal conductivity of 300 to 500 W / (m·K) and a tensile strength of 160 to 220 MPa in an inert atmosphere at room temperature.
[0055] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.
[0056] Example 1
[0057] ① Providing continuous carbon nanotube fibers: The continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .
[0058] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.65g / cm3 .
[0059] ③ Preparation of porous carbon / carbon matrix (carbon nanotube fiber preform with a pyrolytic carbon interface layer): A pyrolytic carbon interface layer is prepared on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition process. The thickness of the interface layer is 1.0 μm, and a carbon nanotube fiber preform with a pyrolytic carbon interface layer is obtained.
[0060] ④ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, the average number of layers is 5, and the SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s; the BN powder is uniformly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor with a solid content of 58% and a viscosity of 76 mPa·s. Solution, specifically, adding boron nitride powder to SiBCN precursor solution for sand milling to obtain a coarse dispersion, and then high-pressure homogenization dispersion of the coarse dispersion to obtain the BN / SiBCN precursor solution, the sand milling time is 40min, the sand milling speed is 2000r / min, the particle size of the zirconium beads used in the sand milling is 1.8mm, and the zirconium bead filling rate is 60%; the pressure of the high-pressure homogenization dispersion (homogenization pressure) is 68MPa, the high-pressure homogenization dispersion time is 30min, and the temperature is 50°C.
[0061] ⑤ Preparation of high thermal conductivity ceramic-based composite materials: Using BN / SiBCN precursor solution as a reactant, a porous carbon / carbon matrix (a carbon nanotube fiber preform with a pyrolytic carbon interface layer) is compounded, and a high thermal conductivity ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the BN / SiBCN precursor solution obtained in step ④ and vacuum impregnation is performed for 60 minutes and pressurized impregnation for 60 minutes in sequence to obtain a material impregnated with the BN / SiBCN precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then the material impregnated with the obtained BN / SiBCN precursor solution was cured in an argon atmosphere, the curing temperature was 220°C, the curing time at 220°C was 120min, and the rate of heating to 220°C was 5°C / min, then the cured material was placed in a reaction device, sealed, evacuated, and introduced argon inert gas with a flow rate of 1000sccm, and the program was set to control the temperature, the heating rate was 5°C / min, and the material was cracked at 1300°C for 120min. After the cracking reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure; the impregnation-curing-cracking process was repeated 10 times to obtain a density of 2.60g / cm 3 A flat plate-shaped high thermal conductivity ceramic matrix composite material.
[0062] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this embodiment was measured to be 356 W / (m·K), and the room temperature tensile strength was measured to be 178 MPa.
[0063] Example 2
[0064] ① Providing continuous carbon nanotube fibers: The continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .
[0065] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.65g / cm 3 .
[0066] ③ Preparation of porous carbon / carbon matrix (carbon nanotube fiber preform with a pyrolytic carbon interface layer): A pyrolytic carbon interface layer is prepared on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition process. The thickness of the interface layer is 0.5 μm, and a carbon nanotube fiber preform with a pyrolytic carbon interface layer is obtained.
[0067] ④ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, the average number of layers is 5, and the SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s; the BN powder is uniformly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor with a solid content of 58% and a viscosity of 76 mPa·s. Solution, specifically, adding boron nitride powder to SiBCN precursor solution for sand milling to obtain a coarse dispersion, and then high-pressure homogenization dispersion of the coarse dispersion to obtain the BN / SiBCN precursor solution, the sand milling time is 40min, the sand milling speed is 2000r / min, the particle size of the zirconium beads used in the sand milling is 1.8mm, and the zirconium bead filling rate is 60%; the pressure of the high-pressure homogenization dispersion (homogenization pressure) is 68MPa, the high-pressure homogenization dispersion time is 30min, and the temperature is 50°C.
[0068] ⑤ Preparation of high thermal conductivity ceramic-based composite materials: Using BN / SiBCN precursor solution as a reactant, a porous carbon / carbon matrix (a carbon nanotube fiber preform with a pyrolytic carbon interface layer) is compounded, and a high thermal conductivity ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the BN / SiBCN precursor solution obtained in step ④ and vacuum impregnation is performed for 60 minutes and pressurized impregnation for 60 minutes in sequence to obtain a material impregnated with the BN / SiBCN precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then the material impregnated with the obtained BN / SiBCN precursor solution was cured in an argon atmosphere, the curing temperature was 220°C, the curing time at 220°C was 120min, the heating rate to 220°C was 5°C / min, and then the cured material was placed in a reaction device, sealed, evacuated, and introduced argon inert gas with a flow rate of 1000sccm. The program was set to control the temperature increase at a heating rate of 5°C / min, and the material was cracked at 1300°C for 120min. After the cracking reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure; the impregnation-curing-cracking process was repeated 10 times to obtain a density of 2.76g / cm 3 A flat plate-shaped high thermal conductivity ceramic matrix composite material.
[0069] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this embodiment was measured to be 403 W / (m·K), and the room temperature tensile strength was measured to be 158 MPa.
[0070] Example 3
[0071] ① Providing continuous carbon nanotube fibers: The continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .
[0072] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.65g / cm 3 .
[0073] ③ Preparation of porous carbon / carbon matrix (carbon nanotube fiber preform with a pyrolytic carbon interface layer): A pyrolytic carbon interface layer is prepared on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition process. The thickness of the interface layer is 1.8 μm, and a carbon nanotube fiber preform with a pyrolytic carbon interface layer is obtained.
[0074] ④ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, the average number of layers is 5, and the SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s; the BN powder is uniformly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor with a solid content of 58% and a viscosity of 76 mPa·s. Solution, specifically, adding boron nitride powder to SiBCN precursor solution for sand milling to obtain a coarse dispersion, and then high-pressure homogenization dispersion of the coarse dispersion to obtain the BN / SiBCN precursor solution, the sand milling time is 40min, the sand milling speed is 2000r / min, the particle size of the zirconium beads used in the sand milling is 1.8mm, and the zirconium bead filling rate is 60%; the pressure of the high-pressure homogenization dispersion (homogenization pressure) is 68MPa, the high-pressure homogenization dispersion time is 30min, and the temperature is 50°C.
[0075] ⑤ Preparation of high thermal conductivity ceramic-based composite materials: Using BN / SiBCN precursor solution as a reactant, a porous carbon / carbon matrix (a carbon nanotube fiber preform with a pyrolytic carbon interface layer) is compounded, and a high thermal conductivity ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the BN / SiBCN precursor solution obtained in step ④, and vacuum impregnation is performed for 60 minutes and pressurized impregnation is performed for 60 minutes in sequence to obtain a material impregnated with the BN / SiBCN precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 100Pa. The material impregnated with the obtained BN / SiBCN precursor solution was cured in an argon atmosphere at a curing temperature of 220°C, a curing time of 120 min at 220°C, and a heating rate of 5°C / min to 220°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with argon inert gas at a flow rate of 1000 sccm. The program was set to control the temperature at a heating rate of 5°C / min, and the material was cracked at 1300°C for 120 min. After the cracking reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure. The impregnation-curing-cracking process was repeated 10 times to obtain a density of 2.28 / cm 3 A flat plate-shaped high thermal conductivity ceramic matrix composite material.
[0076] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this embodiment was measured to be 319 W / (m·K), and the room temperature tensile strength was measured to be 196 MPa.
[0077] Example 4
[0078] ① Providing continuous carbon nanotube fibers: The continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .
[0079] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.65g / cm 3 .
[0080] ③ Preparation of porous carbon / carbon matrix (carbon nanotube fiber preform with a pyrolytic carbon interface layer): A pyrolytic carbon interface layer is prepared on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition process. The thickness of the interface layer is 0.06 μm, and a carbon nanotube fiber preform with a pyrolytic carbon interface layer is obtained.
[0081] ④ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, the average number of layers is 5, and the SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s. The BN powder is uniformly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor with a solid content of 58% and a viscosity of 76 mPa·s. The BN / SiBCN precursor solution is prepared by adding boron nitride to a SiBCN precursor solution and performing sand milling to obtain a coarse dispersion, and then performing high-pressure homogenization to disperse the coarse dispersion to obtain the BN / SiBCN precursor solution. The sand milling time is 40 min, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure of the high-pressure homogenization dispersion (homogenization pressure) is 68 MPa, the high-pressure homogenization dispersion time is 30 min, and the temperature is 50°C.
[0082] ⑤ Preparation of high thermal conductivity ceramic-based composite materials: Using BN / SiBCN precursor solution as a reactant, a porous carbon / carbon matrix (a carbon nanotube fiber preform with a pyrolytic carbon interface layer) is compounded, and a high thermal conductivity ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the BN / SiBCN precursor solution obtained in step ④, and vacuum impregnation is performed for 60 minutes and pressurized impregnation is performed for 60 minutes in sequence to obtain a material impregnated with the BN / SiBCN precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then the material impregnated with the obtained BN / SiBCN precursor solution was cured in an argon atmosphere, the curing temperature was 220°C, the curing time at 220°C was 120min, and the rate of heating to 220°C was 5°C / min, then the cured material was placed in a reaction device, sealed, evacuated, and argon inert gas was introduced at a flow rate of 1000sccm, and the program was set to control the temperature increase at a rate of 5°C / min, and the material was cracked at 1300°C for 120min. After the cracking reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and restored to atmospheric pressure; the impregnation-curing-cracking process was repeated 10 times to obtain a density of 2.88g / cm 3 A flat plate-shaped high thermal conductivity ceramic matrix composite material.
[0083] The room temperature thermal conductivity of the ceramic-based composite material with high thermal conductivity prepared in this embodiment was measured to be 513 W / (m·K), and the room temperature tensile strength was measured to be 104 MPa.
[0084] Example 5
[0085] ① Providing continuous carbon nanotube fibers: The continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .
[0086] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.65g / cm 3 .
[0087] ③ Preparation of porous carbon / carbon matrix (carbon nanotube fiber preform with a pyrolytic carbon interface layer): A pyrolytic carbon interface layer is prepared on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition process. The thickness of the interface layer is 3.0 μm, and a carbon nanotube fiber preform with a pyrolytic carbon interface layer is obtained.
[0088] ④ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, the average number of layers is 5, and the SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s; the BN powder is uniformly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor with a solid content of 58% and a viscosity of 76 mPa·s. Solution, specifically, adding boron nitride powder to SiBCN precursor solution for sand milling to obtain a coarse dispersion, and then high-pressure homogenization dispersion of the coarse dispersion to obtain the BN / SiBCN precursor solution, the sand milling time is 40min, the sand milling speed is 2000r / min, the particle size of the zirconium beads used in the sand milling is 1.8mm, and the zirconium bead filling rate is 60%; the pressure of the high-pressure homogenization dispersion (homogenization pressure) is 68MPa, the high-pressure homogenization dispersion time is 30min, and the temperature is 50°C.
[0089] ⑤ Preparation of high thermal conductivity ceramic-based composite materials: Using BN / SiBCN precursor solution as a reactant, a porous carbon / carbon matrix (a carbon nanotube fiber preform with a pyrolytic carbon interface layer) is compounded, and a high thermal conductivity ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the BN / SiBCN precursor solution obtained in step ④ and vacuum impregnation is performed for 60 minutes and pressurized impregnation for 60 minutes in sequence to obtain a material impregnated with the BN / SiBCN precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then the material impregnated with the obtained BN / SiBCN precursor solution was cured in an argon atmosphere, the curing temperature was 220°C, the curing time at 220°C was 120min, the heating rate to 220°C was 5°C / min, and then the cured material was placed in a reaction device, sealed, evacuated, and introduced argon inert gas with a flow rate of 1000sccm. The program was set to control the temperature, the heating rate was 5°C / min, and the material was cracked at 1300°C for 120min. After the cracking reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure; the impregnation-curing-cracking process was repeated 10 times to obtain a density of 1.97g / cm 3 A flat plate-shaped high thermal conductivity ceramic matrix composite material.
[0090] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this embodiment was measured to be 259 W / (m·K), and the room temperature tensile strength was 208 MPa.
[0091] It can be seen from the above examples 1 to 5 that compared with example 1, the thickness of the interface layer of example 2 is reduced from 1.0 μm to 0.5 μm, and its internal pore size becomes larger, which can be filled with more BN / SiBCN. At the same time, the content of BN is increased, and its thermal properties also change significantly, the thermal conductivity is increased from 356 W / m·K to 403 W / m·K, and the room temperature tensile strength is reduced from 178 MPa to 158 MPa. Compared with example 1, the thickness of the interface layer of example 3 is increased from 1.0 μm to 1.8 μm, and its internal pore size becomes smaller, the content of BN / SiBCN that can be filled is reduced, and the content of BN is also reduced, and its thermal performance is significantly reduced, the thermal conductivity is reduced from 356 W / m·K to 319 W / m·K, and the thickness of the interface layer is increased, which helps to improve the mechanical properties of the composite material, and the room temperature tensile strength is increased from 178 MPa to 196 MPa. Compared with Example 1, the thickness of the interface layer of Example 4 is reduced from 1.0 μm to 0.06 μm, and its internal pore size becomes larger, and more BN / SiBCN can be filled. At the same time, the content of BN is increased, and its thermal properties are also significantly changed, and the thermal conductivity is increased from 356 W / m·K to 513 W / m·K, but the buffer layer of carbon nanotube fiber and ceramic matrix is weak, which makes the mechanical properties of the composite material poor, and the room temperature tensile strength is reduced from 178 MPa to 104 MPa. Compared with Example 1, the thickness of the interface layer of Example 5 is increased from 1.0 μm to 3.0 μm, and its internal pore size is significantly reduced, and the content of BN / SiBCN that can be filled is reduced, and the content of BN is also reduced, and its thermal performance is significantly reduced, and the thermal conductivity is reduced from 356 W / m·K to 259 W / m·K. At the same time, the thickness of the interface layer increases, and the mechanical properties of the composite material are also affected, and the room temperature tensile strength is increased from 178 MPa to 208 MPa.
[0092] Embodiments 6 to 11
[0093] Examples 6 to 11 are basically the same as Example 1. The specific process parameters and the properties of the finally prepared high thermal conductivity ceramic-based composite material are shown in Table 1 below. The other preparation processes are the same as those in Example 1.
[0094] Table 1
[0095]
[0096]
[0097] It can be seen from Table 1 that compared with Example 1, the solid content of the BN / SiBCN precursor solution of Example 6 is reduced from 58% to 51%, wherein the content of BN is reduced, resulting in significant changes in the thermal properties, the thermal conductivity is reduced from 356 W / m·K to 317 W / m·K, and the viscosity of the BN / SiBCN precursor solution is reduced from 76 mPa·s to 57 mPa·s, which improves the density and also helps to improve the mechanical properties, and the room temperature tensile strength is increased from 178 MPa to 183 MPa. Compared with Example 1, the solid content of the BN / SiBCN precursor solution of Example 7 is increased from 58% to 63%, and the increase in the content of BN leads to significant changes in thermal and mechanical properties. The thermal conductivity is increased from 356W / m·K to 381W / m·K, and the viscosity of the BN / SiBCN precursor solution is increased from 76mPa·s to 92mPa·s, which reduces the density and reduces the room temperature tensile strength from 178MPa to 171MPa. Compared with Example 1, the density of the carbon nanotube fiber preform of Example 10 is increased from 0.65g / cm 3 Reduced to 0.5g / cm 3 , so that more BN / SiBCN can fill the pores, but the volume content of carbon nanotube fibers is reduced, resulting in a decrease in thermal conductivity from 356W / m·K to 337W / m·K. Similarly, due to the decrease in the volume content of carbon nanotube fibers, the room temperature tensile strength is reduced from 178MPa to 152MPa. Compared with Example 1, the density of the carbon nanotube fiber preform of Example 11 is reduced from 0.65g / cm 3 Increased to 0.9g / cm 3 , which reduces the volume content of BN / SiBCN, but increases the volume content of carbon nanotube fibers, which increases the thermal conductivity from 356W / m·K to 473W / m·K. Similarly, due to the increase in the volume content of carbon nanotube fibers, the room temperature tensile strength increases from 178MPa to 216MPa.
[0098] Example 12
[0099] ① Provide continuous carbon nanotube fibers and PAN-based continuous carbon fibers: the continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .
[0100] ② Braided carbon nanotube fiber / carbon fiber bidirectional cloth: Continuous carbon nanotube fibers and PAN-based carbon fibers are mixed to obtain carbon nanotube fiber / carbon fiber bidirectional cloth, so that the carbon nanotube fibers and PAN-based carbon fibers are vertically distributed, and the surface density of the obtained carbon nanotube fiber / carbon fiber bidirectional cloth is 350g / m 2 .
[0101] ③ Braiding pointed wedge-shaped carbon nanotube fiber preform: A stacking and stitching process is adopted to weave a carbon nanotube fiber / carbon fiber bidirectional cloth to obtain a pointed wedge-shaped carbon nanotube fiber preform, specifically: firstly, the carbon nanotube fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the carbon nanotube fiber, and then a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped carbon nanotube fiber preform; when stacking, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloth correspond to the tips, and the thick ends correspond to the thick ends, and then the stacked plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stitched into one body by using PAN-based carbon fiber; the volume ratio of carbon nanotube fiber to PAN-based carbon fiber in the obtained pointed wedge-shaped carbon nanotube fiber preform is 2:1, and the density of the pointed wedge-shaped carbon nanotube fiber preform is 0.72 g / cm 3 .
[0102] ④ Preparation of pyrolytic carbon interface layer: A pyrolytic carbon interface layer with a thickness of 1.0 μm is deposited on the fiber surface of the pointed wedge-shaped carbon nanotube fiber preform obtained in step ③ by chemical vapor deposition to obtain a pointed wedge-shaped carbon nanotube fiber preform with a pyrolytic carbon interface layer.
[0103] ⑤ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, the average number of layers is 5, and the SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s; the BN powder is evenly dispersed in the SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor with a solid content of 58% and a viscosity of 76 mPa·s. Solution, specifically, adding boron nitride powder to SiBCN precursor solution for sand milling to obtain a coarse dispersion, and then high-pressure homogenization dispersion of the coarse dispersion to obtain the BN / SiBCN precursor solution, the sand milling time is 40min, the sand milling speed is 2000r / min, the particle size of the zirconium beads used in the sand milling is 1.8mm, and the zirconium bead filling rate is 60%; the pressure of the high-pressure homogenization dispersion (homogenization pressure) is 68MPa, the high-pressure homogenization dispersion time is 30min, and the temperature is 50°C.
[0104] ⑥ Preparation of high thermal conductivity ceramic matrix composite material: Using BN / SiBCN precursor solution as reactant, compounding with a sharp wedge-shaped carbon nanotube fiber preform with a pyrolytic carbon interface layer, and preparing a high thermal conductivity ceramic matrix composite material through a precursor impregnation pyrolysis process, wherein the precursor impregnation pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the sharp wedge-shaped carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ④ in the BN / SiBCN precursor solution obtained in step ⑤, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the BN / SiBCN precursor solution, wherein the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1. 5MPa; then the material impregnated with the obtained BN / SiBCN precursor solution is cured in an argon atmosphere, the curing temperature is 220°C, the curing time at 220°C is 120min, and the heating rate to 220°C is 5°C / min; then the cured material is placed in a reaction device, sealed, evacuated, and argon inert gas is introduced at a flow rate of 1000sccm; the program is set to control the temperature at a heating rate of 5°C / min, and the material is cracked at 1300°C for 120min. After the cracking reaction is completed, the temperature is lowered at a rate of 10°C / min, and the material is cooled to room temperature. The argon inert gas is turned off and the material is restored to atmospheric pressure; the impregnation-curing-cracking process is repeated 10 times to obtain a pointed wedge-shaped high thermal conductivity ceramic-based composite material.
[0105] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this embodiment in the direction of the carbon nanotube fibers was measured to be 344 W / m·K, and the room temperature tensile strength in the direction of the carbon nanotube fibers was 175 MPa.
[0106] Comparative Example 1
[0107] Comparative Example 1: A flat plate-shaped ceramic-based composite material with high thermal conductivity is obtained by the same method as in Example 1, and then a pointed wedge-shaped ceramic-based composite material with high thermal conductivity is machined.
[0108] The room temperature thermal conductivity of the pointed wedge-shaped high thermal conductivity ceramic-based composite material prepared in this comparative example was measured to be 231 W / m·K, and the room temperature tensile strength was measured to be 141 MPa.
[0109] Comparative Example 2
[0110] ①Same as step ① of Example 12.
[0111] ②Same as step ② of Example 12.
[0112] ③ Braided flat carbon nanotube fiber preform: A flat carbon nanotube fiber preform is obtained by weaving carbon nanotube fiber / carbon fiber bidirectional cloth using a lamination and stitching process. Specifically, multiple carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched together to obtain a flat carbon nanotube fiber preform with a volume ratio of carbon nanotube fiber to PAN-based carbon fiber of 2:1. The density of the flat carbon nanotube fiber preform is 0.72 g / cm 3 ; The flat-plate-shaped carbon nanotube fiber preform obtained in step ③ is used to replace the pointed wedge-shaped carbon nanotube fiber preform in Example 12 to carry out the same subsequent steps ④, step ⑤ and step ⑥ as in Example 12.
[0113] The room temperature thermal conductivity of the flat plate-shaped high thermal conductivity ceramic-based composite material prepared in this comparative example in the direction of the carbon nanotube fibers was measured to be 347 W / m·K, and the room temperature tensile strength in the direction of the carbon nanotube fibers was 177 MPa.
[0114] In this comparative example, the flat plate-shaped high thermal conductivity ceramic-based composite material is also machined into a pointed wedge-shaped high thermal conductivity ceramic-based composite material, and the room temperature thermal conductivity of the prepared pointed wedge-shaped high thermal conductivity ceramic-based composite material in the carbon nanotube fiber direction is measured to be 226 W / m·K, and the room temperature tensile strength in the carbon nanotube fiber direction is 136 MPa.
[0115] Although the performance of the flat-plate-shaped high thermal conductivity ceramic-based composite material prepared in this comparative example is basically consistent with the pointed wedge-shaped high thermal conductivity ceramic-based composite material prepared in Example 12, when the flat-plate-shaped high thermal conductivity ceramic-based composite material prepared in this comparative example is processed into a pointed wedge-shaped high thermal conductivity ceramic-based composite material by traditional machining, this traditional method will cause the fibers in the tip area of the product to no longer be continuous, resulting in a significant decrease in the thermal conductivity and mechanical properties of the pointed wedge-shaped high thermal conductivity ceramic-based composite material.
[0116] Comparative Example 3
[0117] ①Same as step ① of Example 1.
[0118] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.9g / cm 3 .
[0119] ③ is the same as step ③ of Example 1.
[0120] ④ Preparation of BN / SiBCN precursor solution: The particle size (average particle size) of the boron nitride powder (BN powder) used is 0.3 μm, and the average number of layers is 5 layers. The SiBCN precursor solution used is prepared from xylene and polyborosilazane. The solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s. Add BN powder to the SiBCN precursor solution and stir for 40 minutes at a stirring speed of 400 rpm, and then ultrasonically treat for 50 minutes at a frequency of 20 kHz to obtain a BN / SiBCN precursor solution with a solid content of 58%.
[0121] ⑤Same as step ⑤ of Example 1.
[0122] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this comparative example was measured to be 411 W / m·K, and the room temperature tensile strength was 188 MPa.
[0123] Comparative Example 4
[0124] ①Same as step ① of Example 1.
[0125] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.9g / cm 3 .
[0126] ③ is the same as step ③ of Example 1.
[0127] ④Preparing SiBCN precursor solution: The SiBCN precursor solution is prepared from xylene and polyborosilazane, and the solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s.
[0128] ⑤ Preparation of high thermal conductivity ceramic matrix composite material: The SiBCN precursor solution prepared in step ④ is used as a reactant to compound the porous carbon / carbon matrix (carbon nanotube fiber preform with a pyrolytic carbon interface layer), and a high thermal conductivity ceramic matrix composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the SiBCN precursor solution obtained in step ④ and vacuum impregnated for 60 minutes and pressurized for 60 minutes in sequence to obtain a material impregnated with the SiBCN precursor solution, wherein the vacuum impregnation pressure is 200Pa and the pressurized impregnation pressure is 1. 5MPa; then the material impregnated with the obtained SiBCN precursor solution is cured in an argon atmosphere, the curing temperature is 220°C, the curing time at 220°C is 120min, the heating rate to 220°C is 5°C / min, and then the cured material is placed in a reaction device, sealed, evacuated, and argon inert gas is introduced with a flow rate of 1000sccm. The program is set to control the temperature at a heating rate of 5°C / min, and the material is cracked at 1300°C for 120min. After the cracking reaction is completed, the temperature is lowered at a rate of 10°C / min, and the material is cooled to room temperature. The argon inert gas is turned off and the pressure is restored to atmospheric pressure. The impregnation-curing-cracking process is repeated 10 times to obtain a flat-plate-shaped ceramic-based composite material with high thermal conductivity.
[0129] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this comparative example was measured to be 382 W / m·K.
[0130] Comparative Example 5
[0131] ①Same as step ① of Example 1.
[0132] ② Braided carbon nanotube fiber preform: The continuous carbon nanotube fiber is braided by puncture to obtain a flat carbon nanotube fiber preform with a density of 0.9g / cm 3 .
[0133] ③ is the same as step ③ of Example 1.
[0134] ④ Prepare an expanded boron nitride modified SiBCN precursor solution: disperse boron nitride powder (average particle size of 0.3 μm, average number of layers of 5 layers) in a sodium hydroxide solution (the mass ratio of boron nitride powder to sodium hydroxide is 1:10, and the concentration of the sodium hydroxide solution is 10 g / mL), and place it in a high-temperature and high-pressure reactor for high-temperature and high-pressure reaction (the temperature of the high-temperature and high-pressure reaction is 300°C, the pressure is 3.5 MPa, and the time is 120 min) to obtain expanded boron nitride; the SiBCN precursor solution used is prepared from xylene and polyborosilazane, and the solid content of the SiBCN precursor solution is 45% and the viscosity is 10 mPa·s; the expanded boron nitride is loaded into a round-bottom flask, the SiBCN precursor solution is loaded into a long-necked funnel, the round-bottom flask and the long-necked funnel are sealed, and a vacuum is drawn using a vacuum pump. After the vacuum degree in the device reaches 10Pa and stabilizes for 5 minutes, the SiBCN precursor solution in the long-necked funnel is slowly dripped into the round-bottom flask containing expanded boron nitride, and the dripping speed is 20mL / min. The round-bottom flask in the vacuum is placed in an ultrasonic device for ultrasonic mixing, and the ultrasonic time is 10 minutes to obtain a SiBCN precursor solution modified with expanded boron nitride having a solid content of 58%; in the SiBCN precursor solution modified with expanded boron nitride in this comparative example, the SiBCN precursor molecules cannot be effectively filled into the expanded boron nitride interlayer. At the same time, due to the lack of sand grinding and high-pressure homogenization dispersion technology, the expanded boron nitride does not form a strong π-π intermolecular force with the SiBCN precursor molecules, resulting in obvious agglomeration, and the effective dispersion of the expanded boron nitride cannot be achieved.
[0135] ⑤ Preparation of high thermal conductivity ceramic-based composite materials: Using the expanded boron nitride modified SiBCN precursor solution as a reactant, a porous carbon / carbon matrix (a carbon nanotube fiber preform with a pyrolytic carbon interface layer) is compounded, and a high thermal conductivity ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the carbon nanotube fiber preform with a pyrolytic carbon interface layer obtained in step ③ is placed in the expanded boron nitride modified SiBCN precursor solution obtained in step ④, and vacuum impregnation is performed for 60 minutes and pressurized impregnation for 60 minutes in sequence to obtain a material impregnated with the expanded boron nitride modified SiBCN precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 200Pa. The pressure is 1.5MPa; then the material impregnated with the obtained expanded boron nitride modified SiBCN precursor solution is cured in an argon atmosphere, the curing temperature is 220°C, the curing time at 220°C is 120min, and the rate of heating to 220°C is 5°C / min. Then the cured material is placed in a reaction device, sealed, evacuated, and argon inert gas is introduced with a flow rate of 1000sccm. The program is set to control the temperature at a heating rate of 5°C / min, and the material is cracked at 1300°C for 120min. After the cracking reaction is completed, the temperature is lowered at a rate of 10°C / min, and the material is cooled to room temperature. The argon inert gas is turned off and the pressure is restored to atmospheric pressure. The impregnation-curing-cracking process is repeated 10 times to obtain a flat-plate-shaped high thermal conductivity ceramic-based composite material.
[0136] The room temperature thermal conductivity of the high thermal conductivity ceramic-based composite material prepared in this comparative example was measured to be 391 W / m·K, and the room temperature tensile strength was 181 MPa.
[0137] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high thermal conductivity ceramic-based composite material, characterized in that: The method comprises the following steps: (1) preparing a carbon nanotube fiber preform; (2) preparing a pyrolytic carbon interface layer on the fiber surface of the carbon nanotube fiber preform by chemical vapor deposition to obtain a carbon nanotube fiber preform having a pyrolytic carbon interface layer; (3) uniformly dispersing boron nitride in a SiBCN precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a BN / SiBCN precursor solution; (4) reacting the BN / SiBCN precursor solution with the carbon nanotube fiber preform having a pyrolytic carbon interface layer obtained in step (3) through a precursor impregnation and cracking process to obtain a ceramic-based composite material with high thermal conductivity.
2. The preparation method according to claim 1, characterized in that: In step (1): the carbon nanotube fiber preform uses a carbon nanotube fiber with a thermal conductivity of 400 to 1000 W / (m·K), a tensile strength of 3 to 5 GPa, and an elongation at break of 2.5 to 4%; In step (1): the density of the carbon nanotube fiber preform is 0.5-0.9 g / cm 3 ; and / or In step (2): the thickness of the pyrolytic carbon interface layer is 0.1 to 2 μm.
3. The preparation method according to claim 1, characterized in that: Step (3) is: Adding boron nitride to the SiBCN precursor solution and performing sand milling to obtain a coarse dispersion, and then performing high-pressure homogenization dispersion on the coarse dispersion to obtain a fine dispersion, namely the BN / SiBCN precursor solution; The sand milling time is 30-60 minutes, the sand milling speed is 1000-3000 r / min, the particle size of the zirconium beads used in the sand milling is 1-3 mm, and the zirconium bead filling rate is 50-70%; The pressure of the high-pressure homogenization dispersion is 35-100 MPa, the time of the high-pressure homogenization dispersion is 15-60 min, and the temperature is 25-60° C.
4. The preparation method according to claim 1, characterized in that: In step (3): The boron nitride is a few-layer boron nitride, the particle size of the few-layer boron nitride is 0.1-1 μm, and the number of layers is 1 to 10; The SiBCN precursor solution has a solid content of 45% and a viscosity of 10 mPa·s; and / or The BN / SiBCN precursor solution has a solid content of 50-65% and a viscosity of 50-100 mPa·s.
5. The preparation method according to claim 1, characterized in that: Step (4) includes the following sub-steps: (a) placing the carbon nanotube fiber preform having a pyrolytic carbon interface layer obtained in step (3) in a BN / SiBCN precursor solution and immersing it for 30 to 360 minutes to obtain a material impregnated with a BN / SiBCN precursor; preferably, the impregnation is vacuum impregnation and pressure impregnation; (b) curing the material impregnated with the BN / SiBCN precursor solution, and then placing it in a reaction device, sealing it, evacuating it, introducing an inert gas, and pyrolyzing it at 1000-1500° C. for 20-200 min; preferably, the curing is performed at 150-350° C. for 30-360 min; (c) after the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped, and the pressure is restored to atmospheric pressure; (d) Repeating steps (a) to (c) at least once, preferably 1 to 10 times.
6. The preparation method according to any one of claims 1 to 5, characterized in that In step (1): The carbon nanotube fiber preform is a pointed wedge-shaped carbon nanotube fiber preform, and the pointed wedge-shaped carbon nanotube fiber preform is prepared as follows: The carbon nanotube fiber and PAN-based carbon fiber are mixed to obtain a carbon nanotube fiber / carbon fiber bidirectional cloth, and then the carbon nanotube fiber / carbon fiber bidirectional cloth is made into a pointed wedge-shaped carbon nanotube fiber preform by a lamination and stitching process.
7. The preparation method according to claim 6, characterized in that: In the carbon nanotube fiber / carbon fiber bidirectional fabric, the carbon nanotube fibers and the PAN-based carbon fibers are vertically distributed; and / or The surface density of the carbon nanotube fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 .
8. The preparation method according to claim 6, characterized in that: The lamination and sewing process comprises: firstly folding the carbon nanotube fiber / carbon fiber bidirectional cloth in a direction perpendicular to the carbon nanotube fiber, and then laminating and sewing a plurality of the folded carbon nanotube fiber / carbon fiber bidirectional cloths to obtain a pointed wedge-shaped carbon nanotube fiber preform; and / or The volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers in the pointed wedge-shaped carbon nanotube fiber preform is (1-3): (1-3); and / or The density of the pointed wedge-shaped carbon nanotube fiber preform is 0.6-0.9 g / cm 3 .
9. A ceramic-based composite material with high thermal conductivity obtained by the preparation method according to any one of claims 1 to 8.
10. The high thermal conductivity ceramic matrix composite material according to claim 9, characterized in that: The density of the high thermal conductivity ceramic-based composite material is 2.2-2.8 g / cm 3 ; and / or The high thermal conductivity ceramic-based composite material has a thermal conductivity of 300 to 500 W / (m·K) at room temperature and a tensile strength of 160 to 220 MPa.
Citation Information
Cited By
Preparation method of high-thermal-conductivity Cf / SiC composite material
CN120463516A